The effect of hormones on an uncommon breast disorder pseudoangiomatous stromal hyperplasia: a case report and literature review. Issue 12 (26th December 2020) - Hattingh, Genevieve; Ibrahim, Mariam; Robinson, Thomas; Shah, Ajay
Abstract: Pseudoangiomatous stromal hyperplasia (PASH) is a benign proliferation of the breast, with few cases reported to date. While the etiology of the disease is uncertain, a prevailing theory is that PASH is hormonally responsive, especially in the presence of progesterone. Literature review shows a correlation between PASH development and oral contraceptive pill (OCP) use. We report a case of a 28-year-old autistic female who underwent excision of palpable bilateral breast masses where the histology of the left breast mass identified as PASH. Our patient had a history of multiple medications including OCPs and cytochrome p450 inhibitors that could lead to an increase in progesterone levels. Thus, supporting a theory that medications, in addition to OCPs, may lead to an increased occurrence of PASH in pre-menopausal women.